The Simulation of Situation Models Aids Analogical Transfer Between Algebra Problems - Minervino, Ricardo Adrian (2016)
Several studies on analogical transfer to algebra word problems have demonstrated that adapting solutions learned from worked-examples to non-isomorphic problems of the same type is challenging, and that most instructional aids do not alleviate this difficulty. At the same time, various authors have suggested that transfer difficulties sometimes originate in students´ lack of disposition to relate algebraic formulae to the real-world situations to which they refer. We designed a non-interactive intervention encouraging students to elaborate situation models for base and target problems, and to ground algebraic formalisms in these representations. One experimental group simulated situation models by physical object manipulation, while another experimental group performed those simulations mentally. Both conditions outperformed a control group that did not run simulations. This intervention was more effective when the transformations posed by target problems were intrinsically more difficult to assimilate into the learned equation. Implications for the design of instructional interventions are discussed.